Air toluene exposure and peripheral neuropathy cases in offset printing in Sleman - Fadhila Pratamasari; Ismail Setyopranoto; Soebijanto Soebijanto (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Air toluene exposure and peripheral neuropathy cases in offset printingPurposeThe purpose of this paper was to determine the relationship between toluene exposure in the air at each workstation in offset printing with the incidence of peripheral neuropathy.MethodsA cross-sectional study was conducted involving total sampling of the offset printing workers who met the criteria. ResultsThe study found that there was no correlation between toluene exposure in the air with the incidence of peripheral neuropathy in offset printing workers in Sleman. Based on the ENMG test, there were only 21.42% workers diagnosed with peripheral neuropathy from 14 workers diagnosed with neuropathy; and it can be ascertained that these were not caused by toluene exposure in the air. ConclusionThere was no correlation between toluene exposure in the air in offset printing with peripheral neuropathy for this study. Weight, length of work, and education were the factors of toluene exposure found in this study. Workers need to pay attention to the limits of the length of exposure.